HISTORY OF CHRONICLES AS AN EDITORIAL WORKS: Editorial analysis of the Book of Chronicles, Ezra and Nehemiah - Pieter Anggiat Napitupulu; Agus Santoso; Bobby Kurnia Putrawan (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2021)
The books of Chronicles (1 and 2 Chronicle), Ezra and Nehemiah usually been understood as three separate  books, written by different authors. But lately The Old Testament experts claim, that these three books were written in a school  called Historical Work of Chronicles or "HWC. There are two groups of  experts  on HWC, namely the first group states that HWC was written in one period by this school , and the second  group HWC was written  stages and  different times (separated by a long period of time) but having the same point of view. This article uses an exegetical study method with an editor-critical approach. The aim of this is to demonstrate the viewpoint of evidence (b) above, that there is a multi-layered editorial process that shows the process of the Chronic Historical Work (which will then be abbreviated as HWC).